Evaluasi Ruang Parkir Off Street di Area Kampus - Greece Maria Lawalata; Athaya Zhafirah; Diki Kurniawan (Jurnal Konstruksi, 2024)
The Garut Institute of Technology (ITG) is one of the universities in Garut Regency which continues to experience growth from year to year in terms of the number of students. Of course, this must be balanced with the provision of adequate facilities, such as parking space. The availability of parking facilities must be able to accommodate the vehicles of students, lecturers, staff and campus visitors. This research aims to evaluate parking spaces at ITG based on the 1998 Technical Guidelines for the Implementation of Parking Facilities for the Director General of Land Transportation. The method used is direct data collection in the field in the form of data on entry and exit of parked vehicles taken in the Odd Semester of the 2022/2023 Academic Year taken in the area campus entrance which is held 2 days per week on Monday and Tuesday which are busy days for lecture activities, namely from 22 May – 6 June 2023 for 9 hours from 07.30 s.d. 16.30. The research results show that the highest parking index value occurred on Tuesday 30 May 2023, namely for cars it reached 125% and for motorbikes it reached 120%, meaning that at that time the need for parking space at ITG exceeded the available capacity. Based on the results of data processing, the current parking demand in off-street parking areas is for cars, namely 20 lots and for motorbikes, 507 parking lots, meaning that there needs to be an additional parking lot for cars of 4 SRP and for motorbikes of 85 SRP. The predicted parking requirement for the next 5 years for cars is 34 SRP and for motorbikes is 851 SRP while the currently available SRP is 16 SRP for cars and 422 for motorbikes so that to meet parking needs in the next 5 years there needs to be an additional 18 SRP for cars and 428 SRP for motorbikes.